sGC stimulator praliciguat suppresses stellate cell fibrotic transformation and inhibits fibrosis and inflammation in models of NASH - Hall, Katherine C. (Proc Natl Acad Sci U S A, 2019)
Endothelial dysfunction and reduced nitric oxide (NO) signaling are a key element of the pathophysiology of nonalcoholic steatohepatitis (NASH). Stimulators of soluble guanylate cyclase (sGC) enhance NO signaling; have been shown preclinically to reduce inflammation, fibrosis, and steatosis; and thus have been proposed as potential therapies for NASH and fibrotic liver diseases. Praliciguat, an oral sGC stimulator with extensive distribution to the liver, was used to explore the role of this signaling pathway in NASH. We found that sGC is expressed in hepatic stellate cells and stellate-derived myofibroblasts, but not in hepatocytes. Praliciguat acted directly on isolated hepatic stellate cells to inhibit fibrotic and inflammatory signaling potentially through regulation of AMPK and SMAD7. Using in vivo microdialysis, we demonstrated stimulation of the NO–sGC pathway by praliciguat in both healthy and fibrotic livers. In preclinical models of NASH, praliciguat treatment was associated with lower levels of liver fibrosis and lower expression of fibrotic and inflammatory biomarkers. Praliciguat treatment lowered hepatic steatosis and plasma cholesterol levels. The antiinflammatory and antifibrotic effects of praliciguat were recapitulated in human microtissues in vitro. These data provide a plausible cellular basis for the mechanism of action of sGC stimulators and suggest the potential therapeutic utility of praliciguat in the treatment of NASH.